2013
DOI: 10.1186/1471-2350-14-96
|View full text |Cite
|
Sign up to set email alerts
|

The TCF7L2 rs7903146 (T) allele is associated with type 2 diabetes in urban Ghana: a hospital-based case–control study

Abstract: BackgroundType 2 diabetes mellitus is increasing dramatically in sub-Saharan Africa, and genetic predisposition is likely involved in that. Yet, genetic variants known to confer increased susceptibility among Caucasians are far from being established in African populations. In Ghanaian adults, we examined associations of several of these polymorphisms with type 2 diabetes.MethodsA hospital-based case–control study on type 2 diabetes (and hypertension) was conducted in Kumasi, Ghana. TCF7L2 rs7903146, KCNJ11 rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
7
24
0
Order By: Relevance
“…While this is the case in other population groups, some studies reported a weak 33,34 or no association [35][36][37][38] . Other studies highlighted the effect of the TCF7L2 polymorphisms on the progression of T2DM 35,39 , in some ethnic population groups these variants were associated with responses to medication 40,41 , and in others their effect on the disease was modulated by the type of diet [42][43][44] .Our results [1.43 (1.00 to 2.04), p= 0.053] are comparable to those reported for other African ethnic population groups 17,18,20 . It is possible that TCF7L2 polymorphisms have different effects in various ethnic population groups depending on the diet.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While this is the case in other population groups, some studies reported a weak 33,34 or no association [35][36][37][38] . Other studies highlighted the effect of the TCF7L2 polymorphisms on the progression of T2DM 35,39 , in some ethnic population groups these variants were associated with responses to medication 40,41 , and in others their effect on the disease was modulated by the type of diet [42][43][44] .Our results [1.43 (1.00 to 2.04), p= 0.053] are comparable to those reported for other African ethnic population groups 17,18,20 . It is possible that TCF7L2 polymorphisms have different effects in various ethnic population groups depending on the diet.…”
Section: Discussionsupporting
confidence: 78%
“…Although few number of T2DM susceptibility genes discovered through candidate gene, linkage analyses, and GWA studies elsewhere have been replicated in African studies [16][17][18][19][20][21] , it must also be emphasized that many other association studies failed to show significant and replicable findings [22][23][24] . Therefore in this study we investigated three genes, namely, TCF7L2, FTO, and ENPP1 as risk factors for T2DM in a South African ethnic population group of Mixed-ancestry (Coloureds) with a unique genetic architecture.…”
Section: Introductionmentioning
confidence: 99%
“…rs7903146 was genome-wide significant as expected from previous T2D studies in Africa 4,[20][21][22][23][24][25] and consistent with the findings of most populations studied around the world. We also replicated several previously reported T2D loci.…”
Section: Discussionsupporting
confidence: 89%
“…After the initial report on the association of a common microsatellite within intron 3 of TCF7L2 (DG10S478) with T2DM (14), successive replication studies conducted in populations of different ethnic origin confirmed the strong association between a number of TCF7L2 polymorphisms, especially rs7903146 and rs12255372, and T2DM (15)(16)(17)(18)(19)(20)(21)(22). Moreover, among Latin American countries there are only reports on the association of TCF7L2 polymorphisms and T2DM from Colombia (23), Brazil (24)(25)(26)(27)(28) and Mexico (9,(29)(30)(31)(32).…”
Section: Tcf7l2 Polymorphisms and Type 2 Diabetes Riskmentioning
confidence: 99%